Dynamic analysis of mechanical systems with planar revolute joints with clearance. (December 2015) - Ma, Jia; Qian, Linfang; Chen, Guangsong; Li, Miao
Abstract: Clearances in mechanical joints are unavoidable due to many uncertainties such as manufacturing tolerances, assemblage, wear, and material deformation. The dynamic characteristics of mechanical systems are greatly affected by the joint clearances during the contact process. Thus, a proper contact force model plays a key role in simulating the overall performance of the mechanical systems. In this paper, a hybrid contact force model is described, which is based on the Lankarani–Nikravesh contact force model and the elastic foundation model. The discrete element theory and Gaussian quadrature are utilized to analyze and simulate the contact process. By distributing the non-uniform bearing points over the pin surface and calculating the penetration of each point individually, the total contact force can be obtained by integrating the discrete ones in the contact area. Some comparisons with the Lankarani–Nikravesh model indicate that the hybrid model is more effective for small clearance and low restitution coefficient situations. Finally, comparison of dynamic characteristics between the numerical simulation results and experimental ones for a revolute clearance joint in the slider–crank mechanism is employed to validate the hybrid model. Highlights: A hybrid contact force model is described based on the Lankarani–Nikravesh model and the elastic foundation model. The discrete element theory and Gaussian quadrature are utilized to analyze and simulate the contact process. The pin surface is discretized into elements in which some bearing points are distributed unevenly. The total contact force can be obtained by integrating the discrete ones. The hybrid model can be applied more effectively for small clearance and low restitution coefficient situations.